2021
DOI: 10.1111/hepr.13735
|View full text |Cite
|
Sign up to set email alerts
|

Screening for portopulmonary hypertension using computed tomography‐based measurements of the main pulmonary artery and ascending aorta diameters in patients with portal hypertension

Abstract: Aim: This study aimed to demonstrate the feasibility of identifying candidates of portopulmonary hypertension (PoPH) from general portal hypertension patients based on chest computed tomography (CT) results. Methods: One hundred and thirty patients with portal hypertension who had undergone interventional radiology therapies at our hospital between August 2011 and July 2021 were included, and preoperative clinical data were collected. Suspicious PoPH was defined as main pulmonary artery diameter (mPA-D) ≥ 29 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…A study from Japan reported that female gender, higher shortest diameter of the inferior vena cava, presence of portosystemic shunts of ≥ 5 mm, and lower blood urea nitrogen levels were independent factors related to PoPH in 130 patients with portal hypertension [24]. It has also been reported from studies conducted in other countries that the incidence of PoPH is signi cantly higher in female patients than in male patients [10,13,30,31].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study from Japan reported that female gender, higher shortest diameter of the inferior vena cava, presence of portosystemic shunts of ≥ 5 mm, and lower blood urea nitrogen levels were independent factors related to PoPH in 130 patients with portal hypertension [24]. It has also been reported from studies conducted in other countries that the incidence of PoPH is signi cantly higher in female patients than in male patients [10,13,30,31].…”
Section: Discussionmentioning
confidence: 94%
“…Non-invasive examinations have been reported as auxiliary methods for predicting PoPH. Subjective symptoms (such as shortness of breath), serum brain natriuretic peptide (BNP) measurement, and measurement of the main pulmonary artery diameter have been reported have utility in the early detection of PoPH [22][23][24]. Measurement of the tricuspid regurgitation pressure gradient (TRPG) values by echocardiography is recommended as the most objective examination for the detection of PoPH [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for early diagnosis and severity of POPH have been recently reported in these patients. 18,19 However, the management of POPH remains uncertain, as the pathophysiology is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The development of POPH related to end‐stage liver disease and cirrhosis has been a subject of debate for many years. Various methods for early diagnosis and severity of POPH have been recently reported in these patients 18,19 . However, the management of POPH remains uncertain, as the pathophysiology is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous studies, CT angiography is a good exam for visualizing the different branches of arteries and studying the anatomic variations in their origin, especially in the case of uterine arteries [14,32] . CT demonstrates good penetration, can clearly show certain organs and arteries, has great potential for exploring smaller branches of blood vessels, and can be used to diagnose vascular diseases such as stenosis and occlusion [33][34] . Therefore, in this study, we used CT imaging to observe changes in the diameter of the uterine and peripheral arteries to evaluate changes in placental perfusion and peripheral resistance.…”
Section: Discussionmentioning
confidence: 99%